\(E\)-Convex programming - Liana Lupşa; Dorel Duca (Journal of Numerical Analysis and Approximation Theory, 2004)
In [6] one shows that some of the results obtained in [5] on \(E\)-convex programming are incorrect. In this paper we recover these results in the new hypotheses.